2006
DOI: 10.1002/ajh.20756
|View full text |Cite
|
Sign up to set email alerts
|

Congenital amegakaryocytic thrombocytopenia—Report of a new c‐mpl gene missense mutation

Abstract: A 44-month old girl with congenital amegakaryocytic thrombocytopenia, already with pancytopenia, underwent an unrelated allogeneic cord blood transplantation with recovery of normal blood cell counts. The patient was a compound heterozygote for two c-mpl missense mutations inherited from both parents, one of them, a G578A exon 4 mutation leading to a cysteine to tyrosine replacement of codon 193, previously unreported. Am. J. Hematol. 82:240-241, 2007. V V C 2006 Wiley-Liss, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 5 publications
1
13
0
1
Order By: Relevance
“…1,[4][5][6][7][8][9][10][11] However, the diagnosis of five patients in two centers during the last 2 years raises the suspicion that the incidence of the disease is underestimated, presumably because the initial presentation of CAMT with isolated thrombocytopenia can be easily misdiagnosed with idiopathic thrombocytopenic purpura, while the late pancytopenic phase is indistinguishable from aplastic anemia. Thus, bone marrow examination should be part of the diagnostic work-up in all children with severe thrombocytopenia since birth and screening of the c-MPL gene should be performed when a reduced number of megakaryocytes is observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,[4][5][6][7][8][9][10][11] However, the diagnosis of five patients in two centers during the last 2 years raises the suspicion that the incidence of the disease is underestimated, presumably because the initial presentation of CAMT with isolated thrombocytopenia can be easily misdiagnosed with idiopathic thrombocytopenic purpura, while the late pancytopenic phase is indistinguishable from aplastic anemia. Thus, bone marrow examination should be part of the diagnostic work-up in all children with severe thrombocytopenia since birth and screening of the c-MPL gene should be performed when a reduced number of megakaryocytes is observed.…”
Section: Discussionmentioning
confidence: 99%
“…3 At least 28 different c-MPL mutated alleles have been so far identified from 32 unrelated CAMT families. 1,[4][5][6][7][8][9][10][11] Beside these mutations associated with CAMT, a gain-of-function mutation of c-MPL is responsible for familial essential thrombocythemia. 12 Interestingly, different types of mutations have been associated with different phenotypes, allowing patients to be subdivided into two groups.…”
mentioning
confidence: 99%
“…A small number of patients was asymptomatic at birth and presented with signs of thrombocytopenia or pancytopenia in childhood (Gandhi et al , 2005; Passos‐Coelho et al , 2007; Savoia et al , 2007; Steinberg et al , 2007). Therefore, the diagnosis of CAMT has to be taken into account even in those cases that first present with thrombocytopenia or aplastic anaemia after the first year of life.…”
Section: The Clinical Presentation Of Camtmentioning
confidence: 99%
“…Review of the literature identified nine cases of unrelated SCT in patients with CAMT with detailed transplant information (Table 1) (5, 8, 9, 12–14). Four additional cases were identified that have incomplete details on the age at time of transplant, HLA matching, preparative regimens and were not included in this review (15–18). All nine patients except one received a fully ablative preparative regimen with five receiving TBI.…”
Section: Discussionmentioning
confidence: 99%